The Challenges and Strengths to Ensure the Well-being and Safety of Autistic Children to Meet their Distinct Requirements and Create a Safe and Supportive Environment - Akter, Masuma (Advances in Social Sciences Research Journal, 2024)
This study seeks to broaden our understanding of the challenges and strengths essential for effectively supporting children with autism spectrum disorder (ASD), contributing valuable insights to enhance our approach in addressing their unique needs. A child with special needs may have been born with cognitive disability, critical physical condition, abnormal syndrome, or chronic psychological illness (Autism, ADHD, Down syndrome, Cerebral Palsy, Epilepsy, etc.). He or she may have problems with behavior, communication, or social activities. We always need to keep in mind that each child is unique, so we need to observe and listen to their individual preferences and needs. The study has explored at the prevalence of ASD among children aged between 07-15 years. Methodology: A comprehensive investigation unfolded through both a Case Study and a cross-sectional study, involving 200 children within the age range of 7-15 years. Objective: This study aims to uncover the unique challenges experienced by autistic children and proposes solutions to create a secure and supportive environment on basis of their needs